Professionalism in Popular Music Voice Teacher Education : Institutional Conditions of a Changing Field in Finland and Sweden - Keskinen, Katri A. (Sage, 2025)
There is a need to understand how higher music education can better adapt to changes in societies and professionalism. As a field that embraces change, popular music voice teaching exemplifies how professionalism can expand. Drawing on theories regarding the evolving concept of professionalism, especially in teaching disciplines, this study examines changes in professionalism within popular music-oriented voice teacher education in higher music education and explores how institutional conditions shape these perceptions and the broader development of professionalism. The multiple case study involved two cases in the Nordic context, in Finland and Sweden, where such education has existed for decades. The research material included semi-structured interviews with teacher educators, observations, a researcher diary, and institutional documents. The abductive analyses utilized a previously constructed framework for popular music voice teachers’ expanding professionalism. The findings suggest that the examined voice teacher education programs foster lifelong learning, reflection, resilience, and collaboration, while emphasizing student agency and competence thinking. The article also discusses how institutional values and contexts, territorialism, and the self-replicative systems of institutionalized teacher education may influence professionalism.
Keywords: laulunopettajat; opettajankoulutus; korkea-asteen koulutus; populaarimusiikki; laulumusiikki